A new thieno-isoindigo derivative-based D–A polymer with very low bandgap for high-performance ambipolar organic thin-film transistors1. Issue 21 (7th June 2015) - Zhang, Guobing; Ye, Zhiwei; Li, Peng; Guo, Jinghua; Wang, Qinghe; Tang, Longxiang; Lu, Hongbo; Qiu, Longzhen
<x xml:space="preserve">Abstract</x> A new thieno-isoindigo derivative was synthesized by replacing the outer benzene ring of the isoindigo derivative (BIBDF) with thiophene.